2015
DOI: 10.1093/nop/npv031
|View full text |Cite
|
Sign up to set email alerts
|

Adult patients with supratentorial pilocytic astrocytoma: long-term follow-up of prospective multicenter clinical trial NCCTG-867251 (Alliance)

Abstract: Background Pilocytic astrocytoma is a rare tumor in adults. This report is of a prospective clinical trial with long-term follow-up. Methods Between 1986 and 1994, 20 eligible adults with supratentorial pilocytic astrocytomas were enrolled in a prospective intergroup trial of radiotherapy (RT) after biopsy (3 patients) or observation after gross (11 patients) or subtotal (6 patients) resection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…Of note, earlier series by Ye et al [15] reported up to 20% morbidity, 35% complication frequency and a 10% mortality, which are all higher than numbers reported in our cohort and a possible indication of improvement in surgical care over time. Finally, varying degree of adjuvant treatment has been reported, from 6-22% [14,15,17] with our frequency being 9.3%, which is more in line with overall recommendations from recent literature only to use radiotherapy as salvage [19], further substantiated by the demonstration of prolonged PFS but equal OS between adult patients with pilocytic astrocytoma that underwent GTR with-or without adjuvant radiotherapy [20].…”
Section: Pilocytic Astrocytomasupporting
confidence: 89%
“…Of note, earlier series by Ye et al [15] reported up to 20% morbidity, 35% complication frequency and a 10% mortality, which are all higher than numbers reported in our cohort and a possible indication of improvement in surgical care over time. Finally, varying degree of adjuvant treatment has been reported, from 6-22% [14,15,17] with our frequency being 9.3%, which is more in line with overall recommendations from recent literature only to use radiotherapy as salvage [19], further substantiated by the demonstration of prolonged PFS but equal OS between adult patients with pilocytic astrocytoma that underwent GTR with-or without adjuvant radiotherapy [20].…”
Section: Pilocytic Astrocytomasupporting
confidence: 89%
“…Adjuvant radiation after subtotal resection remains controversial, as the only so far conducted clinical trial did not include patients over 50 years and concentrated on patients with very favorable prognostic factors [25]. Other retrospective series indicate an added clinical benefit of radiation in case of unfavorable prognosis, however based on the limited available data, treatment decisions have to be made on an individual basis and should include tumor-and patient-specific parameters for prognostic assessment [17].…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients, the majority of PAs are located supratentorially [14,18], less commonly in the cerebellum [96,100], cervicomedullary region [103] or other parts of the spinal cord [37,74,86]. Occasionally, PA in adult patients are associated with haemorrhages and manifest as spontaneous intracranial haemorrhage [57,59].…”
Section: Localizationmentioning
confidence: 99%